Patients with Rapid Atrial Fibrillation in Congestive Heart Failure with Bilateral Pleural Effusion Complication: Case Report and Literature Review - Irma Kartikasari; Mochamad Basori; Muhammad Hanun Mahyuddin; Ulaa’ Haniifah; Olga Putri Atsira (Universitas Airlangga, 2023)
Highlights: In the setting of AF in patient with AHF, conventional treatment strategies do not convert the rhythm into sinus rhythm. Newly emerged therapies such as catheter ablation, or atrioventricular node ablation with biventricular pacing might be more beneficial rather than the conventional rhythm and rate control strategies Abstract: Atrial fibrillation (AF) is the most common form of arrhythmia. The prevalence of AF in patients with systolic left ventricular dysfunction and CHF is around 35% in the patient population with NYHA II-IV. In this case, we will discuss a case report of a patient with AF with complications of CHF and Bilateral Pleural Effusion. Case Summary. A female patient, 62 years old, came to the emergency room of dr. Soegiri Hospital with complaints of sudden shortness of breath since morning. There were crackles in the right lung field during the auscultation and the chest x-ray shows cardiomegaly with a CTR> 50% with bilateral effusion and atelectasis. On the electrocardiogram examination performed at the ICCU, an irregular rhythm was obtained with an HR of 100x/minute, with p waves that cannot be distinguished, normal QRS waves, and T waves that cannot be assessed. The patient was diagnosed with congestive heart failure (CHF) with rapid atrial fibrillation (AF) accompanied by complications of bilateral pleural effusion with a differential diagnosis of acute decompensated heart failure (ADHF) with pneumonia and acute lung edema (ALO). Discussion. Patients with AF and CHF have a poorer prognosis than patients with a single diagnosis of AF or CHF alone. A rhythm control strategy consisting of antiarrhythmic drugs and electrical cardioversion in stable patients with AF and CHF adds no benefit to a heart rate control strategy.